RERE deficiency contributes to the development of orofacial clefts in humans and mice. Issue 7 (26th March 2021) - Kim, Bum Jun; Zaveri, Hitisha P; Kundert, Peter N; Jordan, Valerie K; Scott, Tiana M; Carmichael, Jenny; Scott, Daryl A
Abstract: Deletions of chromosome 1p36 are the most common telomeric deletions in humans and are associated with an increased risk of orofacial clefting. Deletion/phenotype mapping, combined with data from human and mouse studies, suggests the existence of multiple 1p36 genes associated with orofacial clefting including SKI, PRDM16, PAX7 and GRHL3 . The arginine–glutamic acid dipeptide (RE) repeats gene ( RERE ) is located in the proximal critical region for 1p36 deletion syndrome and encodes a nuclear receptor co-regulator. Pathogenic RERE variants have been shown to cause neurodevelopmental disorder with or without anomalies of the brain, eye or heart (NEDBEH). Cleft lip has previously been described in one individual with NEDBEH. Here we report the first individual with NEDBEH to have a cleft palate. We confirm that RERE is broadly expressed in the palate during mouse embryonic development, and we demonstrate that the majority of RERE-deficient mouse embryos on C57BL/6 background have cleft palate. We go on to show that ablation of Rere in cranial neural crest (CNC) cells, mediated by a Wnt1-Cre, leads to delayed elevation of the palatal shelves and cleft palate and that proliferation of mesenchymal cells in the palatal shelves is significantly reduced in Rere flox/flox ; Wnt1-Cre embryos. We conclude that loss of RERE function contributes to the development of orofacial clefts in individuals with proximal 1p36 deletions and NEDBEH and that RERE expression in CNC cells and their derivatives is required for normal palatal development.